Recent advances in nano-enabled immunomodulation for enhancing plant resilience against phytopathogens - Masood, Hafiza Ayesha; Qi, Yetong; Zahid, Muhammad Khubaib; Li, Zhitao; Ahmad, Salman; Lv, Ji-Min; Shahid, Muhammad Shafiq; Ali, Hamada E.; Ondrasek, Gabrijel; Qi, Xingjiang (Frontiers in Plant Science, 2024)
Plant diseases caused by microbial pathogens pose a severe threat to global food security. Although genetic modifications can improve plant resistance; however, environmentally sustainable strategies are needed to manage plant diseases. Nano-enabled immunomodulation involves using engineered nanomaterials (ENMs) to modulate the innate immune system of plants and enhance their resilience against pathogens. This emerging approach provides unique opportunities through the ability of ENMs to act as nanocarriers for delivering immunomodulatory agents, nanoprobes for monitoring plant immunity, and nanoparticles (NPs) that directly interact with plant cells to trigger immune responses. Recent studies revealed that the application of ENMs as nanoscale agrochemicals can strengthen plant immunity against biotic stress by enhancing systemic resistance pathways, modulating antioxidant defense systems, activating defense-related genetic pathways and reshaping the plant-associated microbiomes. However, key challenges remain in unraveling the complex mechanisms through which ENMs influence plant molecular networks, assessing their long-term environmental impacts, developing biodegradable formulations, and optimizing targeted delivery methods. This review provides a comprehensive investigation of the latest research on nano-enabled immunomodulation strategies, potential mechanisms of action, and highlights future perspectives to overcome existing challenges for sustainable plant disease management.